2020
DOI: 10.34172/ajcmi.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-Based Regimen Versus Bismuth Quadruple Regimen for Helicobacter pylori Eradication in Kurdistan Region, Iraq

Abstract: Background Helicobacter pylori is a gram-negative bacterium that infects half of the populations worldwide (1). In addition, it can cause gastric and duodenal ulcer and predispose to individuals gastric adenocarcinoma (2). Further, H. pylori infection is persistent while asymptomatic in most individuals. However, whenever the microorganism is diagnosed, it should be eradicated with the administration of antibiotics and the proton pump inhibitor (3). The determinants of the successful eradication of this microo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…H. pylori infection has been studied extensively in Iraq; it has been found to be one of the most common infectious agents causing gastric diseases. 2,[12][13][14][15] In addition, the prevalence of H. pylori infection has been studied in different age groups. 5 However, no study has determined the other potential risk factors associated with this infection.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection has been studied extensively in Iraq; it has been found to be one of the most common infectious agents causing gastric diseases. 2,[12][13][14][15] In addition, the prevalence of H. pylori infection has been studied in different age groups. 5 However, no study has determined the other potential risk factors associated with this infection.…”
Section: Discussionmentioning
confidence: 99%
“…Every Region must do a local survey of bacterial prevalence and susceptibility to make empirical guidelines, to make sure physician prescribe the right Empirical antibiotic which will reduce AMR drastically as misuse of prescription is the biggest cause of resistance. Previously, antibiotic sensitivity patters were studied in Iraq (5, 18-23). It was found that multidrug resistant microorganisms are common in the Iraq (9, 24-28).…”
Section: Introductionmentioning
confidence: 99%